Challenges of conflicting school reforms : effects of New American Schools in a high-poverty district - Berends, Mark, 1962- (Online Rand research documents., 2002)
New American Schools (NAS) offers whole-school designs for schools and districts seeking to significantly raise the achievement of large numbers of students. This work has evaluated NAS reforms' effects on students and teachers in high-poverty schools.